Aplikasi Biopestisida Fobio Terhadap Penyakit Moler (Fusarium oxysporum) Pada Tiga Varietas Bawang Merah Di Kota Probolinggo - Shafa, Yola Salsabila; Wiyatiningsih, Sri; Tri Wahyu Prasetyawati, Endang (BIOEDUSCIENCE, 2024)
Background: Shallots (Allium Ascolonicum L). is a seasonal crop that is widely grown by farmers intensively. Although the demand for productivity of this crop continues to increase, domestic production is still not enough to meet market demand because shallots are a seasonal crop. The low productivity of onion plants can be influenced by various factors, one of which is Fusarium attack, which if not controlled can cause crop failure. The use of chemical pesticides to control Fusarium sp. often causes dependence and pollution, so alternative controls are needed. The purpose of this study was to determine the potential of Fobio Biopesticide against three onion varieties in increasing growth and reducing the intensity of Fusarium sp. attack.Method: The method used is RAKF with a factor of 1 consisting of three varieties of shallots (Biru Lancor, Tajuk, and Batu Ijo), factor 2 in the form of farmer treatment and concentration levels of Biopesticide Fobio 5 and 10 ml / l. Results: The results showed that treatment with a concentration of Biopesticide Fobio 5 ml / l and Blue Lancor varieties was able to increase the best results in various variables such as plant height, wet weight, dry weight, disease intensity, and incubation period. Conclusion: Based on the research that has been done, it can be concluded that Fobio Biopesticide has the capacity to increase the resistance of onion plants to moler disease. Treatment with Biopestiisda Fobio concentration of 5 ml / l in the Lancor Blue onion variety showed the best results in various variables compared to other treatments, it was shown an increase in plant height up to 5 – 6 cm, wet weight up to 2.8 g / tuber, dry weight up to 1.7 g / tuber, disease intensity up to 8% at 42 HST, and the longest incubation period up to 23 days. Keywords: Shallot, Biopesticide Fobio, Fusarium sp.